Biblical stars in medieval Jewish thought (tenth-twelfth centuries) - Selaʿ, Shelomoh 1948- (2015)
The twelfth century witnessed a new Jewish interest in the fixed stars, which finds its major expression in the first-ever Hebrew lists of constellations and fixed stars. These are in fact translations into Hebrew of Arabic lists, which ultimately go back to the star catalogue in Ptolemy"s Almagest. This article focuses on one limited but eye-catching aspect of this intellectual phenomenon: stars names found in the Bible appear in twelfth-century Hebrew lists of fixed stars side by side with other names that are either Hebrew translations or transliterations of the Arabic names. To explain this metamorphosis, we begin with the Scriptural references to stars and look at the Talmudic relevant comments. Then we examine the contribution by Saadia Gaon, who, we argue, was the first to link biblical and Arabic star names. Finally, the bulk of this article is devoted to the role of biblical stars in the writings of Abraham Bar Hiyya and Abraham Ibn Ezra.
Keywords: Ptolemaeus, Claudius -- 100-178; Seʿadyah -- Gaʾon -- 882-942; Ibn-ʿEzra, Avraham Ben-Meʾir -- 1092-1167; Avraham bar-Ḥiyya ha-Naśi -- 1065-1136; Bibel; Astronomie; Arabic names; Asterisms (Astronomy); Stars -- Names; Stars -- Religious aspects; Transliteration